Hi asked in Science & MathematicsMathematics · 3 weeks ago

How do you solve for x in: ln(3)=ln(10)-(0.1)(x)?

4 Answers

Relevance
  • 3 weeks ago
    Favorite Answer

    Solve just like any equation:

    ln(3) = ln(10) - (0.1)(x)

    -0.1x = [ln(3) - ln(10)]

    x = [ln(3) - ln(10)] / -0.1 = 12.03972804

    • ...Show all comments
    • stanschim
      Lv 7
      3 weeks agoReport

      I simply subtracted ln(10) from each side and wrote the equation with the terms reversed from the original problem.  Remember, try to isolate the unknown, x, on the left side of the equation when doing algebra.

    • Log in to reply to the answers
  • Philip
    Lv 6
    3 weeks ago

    ln(3) = ln(10) - (0.1)x, ie. ln(10) - ln(3) = ln(10/3) = (0.1)x. Multiply through

    bt 10 getting x = 10ln(10/3) = 10(1.203972804) = 12.0397804.

    • Log in to reply to the answers
  • Vaman
    Lv 7
    3 weeks ago

    ln(3)=ln(10)-(0.1)(x)?

    0.1x = ln 10 -ln 3=ln 10/3

    10/3= e^(0.1x) =e^(x/10)

    x = 10 ln(10/3)=12.04

    • Log in to reply to the answers
  • ?
    Lv 7
    3 weeks ago

    ln(3) =  ln(10) - (0.1)(x) ⇒

    0.1x = ln 10 - ln 3

    .......ln 10 - ln 3

    x = ---------------

    ............0.1

    ......2.30259 - 1.09861

    x = ------------------------

    ............0.1

    x = 12.0398......................ANS

    • Log in to reply to the answers
Still have questions? Get answers by asking now.